VIPoma with multiple endocrine neoplasia type 1 identified as an atypical gene mutation. (12th November 2015) - Fujiya, Atsushi; Kato, Makoto; Shibata, Taiga; Sobajima, Hiroshi
Abstract : A 47-year-old man presented with persistent diarrhoea and hypokalaemia. CT revealed 4 pancreatic tumours that appeared to be VIPomas, because the patient had an elevated plasma vasoactive intestinal polypeptide level. MRI showed a low-intensity area in the pituitary suggestive of a pituitary tumour, and a parathyroid tumour was detected by ultrasonography and 99Tc-MIBI scintigraphy. Given these results, the patient was diagnosed with multiple endocrine neoplasia type 1 (MEN1) and scheduled for surgery. MEN1 is an autosomal dominant disorder associated with MEN1 mutations. Genetic testing indicated that the patient had a MEN1 gene mutation; his 2 sons had the same mutations. Most MEN1 tumours are benign, but some pancreatic and thymic tumours could become malignant. Without treatment, such tumours would result in earlier mortality. Despite its rarity, we should perform genetic testing for family members of patients with MEN1 to identify mutation carriers and improve the patients' prognosis.